A surface-enhanced Raman spectroscopy substrate based on mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles, preparation method and application.
Patent Information
- Application Number
- CN202611053257.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-20
AI Technical Summary
(1)羧基特异性识别能力不足:抗燃油中酸性产物主要为羧酸类化合物(R-COOH),常规SERS基底(如裸金或银纳米粒子)对羧基(-COOH)缺乏特异性亲和力,难以从复杂的抗燃油基质中精准识别和捕获痕量羧酸分子
本发明一种基于巯基化聚乙二醇/聚二甲基硅氧烷两亲性互穿网络凝胶负载金&银核壳纳米粒子的表面增强拉曼光谱基底制备方法,首先,通过溶胶-凝胶法和交联反应构筑PEG-SH/PDMS两亲性互穿网络凝胶,原因在于,两亲性互穿聚合物网络(AmphiphilicConetworks,APCN)由亲水性聚合物和疏水性聚合物相互贯穿构成,可同时吸收极性和非极性溶质。且聚乙二醇(PEG)与聚二甲基硅氧烷(PDMS)组成的两亲性互穿网络已被证明可形成稳定的微相分离结构,其三维多孔网络可作为纳米粒子合成的微反应器,利用孔道的空间限域效应调控纳米粒子的成核与生长过程。
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of fire-resistant oil performance testing technology, specifically to a surface-enhanced Raman spectroscopy substrate based on mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles, its preparation method, and its application. Background Technology
[0002] Phosphate ester fire-resistant oils are widely used in the electro-hydraulic conditioning systems of critical power equipment such as large steam turbine units and nuclear power plants due to their excellent fire-resistant properties. However, during long-term high-temperature operation, fire-resistant oils undergo thermal oxidation and hydrolytic aging, generating acidic products such as phosphoric acid and organic carboxylic acids, leading to an increase in acid value. Acid value is a core indicator for evaluating the degree of aging of fire-resistant oils. Both GB / T14542—2017 and DL / T571—2014 stipulate that the acid value of fire-resistant oils in operation should be controlled below 0.15 mgKOH / g. Therefore, accurate and rapid on-site testing of the acid value of fire-resistant oils is of great significance for ensuring the safe operation of power equipment.
[0003] Currently, the standard method for detecting the acid value of fire-resistant oil is potentiometric titration (GB / T264). This method requires laboratory testing, is complex and time-consuming (usually >30 minutes), consumes a large amount of sample (>10 mL), and cannot achieve rapid on-site detection. Surface-enhanced Raman spectroscopy (SERS) is considered an ideal means for on-site detection of oil aging characteristics due to its advantages such as high fingerprint recognition characteristics, fast detection speed, immunity to water molecule interference, and small sample consumption. For example, CN119827479A discloses a SERS method for determining the benzotriazole content in mineral insulating oil, which includes the following steps: (1) preparation of a SERS substrate with a hemispherical microcavity structure; (2) surface cleaning of the substrate; (3) pretreatment of the sample to be tested and the standard solution; and (4) detection and quantification.
[0004] For example, CN121495150A discloses a bimetallic dual-network hydrogel SERS sensor, its preparation method, and its application. The preparation method of the hydrogel SERS sensor includes the following steps: first, preparing gold nanoparticles (AuNPs), then preparing silver-coated gold core-shell nanoparticles (Au@AgNPs); concentrating the nanoparticles and loading them proportionally inside an agarose (AG) and sodium alginate (SA) hydrogel; and adding carboxylated cellulose (C-CNF) to stabilize the nanoparticles inside the hydrogel. However, this hydrogel is not amphiphilic and cannot actively enrich polar carboxylic acid molecules from a nonpolar oil phase.
[0005] However, applying SERS technology to the acid value detection of fire-resistant oils still faces the following technical bottlenecks: (1) Insufficient carboxyl-specific recognition ability: The acidic products in fire-resistant oil are mainly carboxylic acid compounds (R-COOH). Conventional SERS substrates (such as bare gold or silver nanoparticles) lack specific affinity for carboxyl groups (-COOH), making it difficult to accurately identify and capture trace carboxylic acid molecules from complex fire-resistant oil matrices.
[0006] (2) Low enrichment efficiency of polar molecules in oil phase: Fire-resistant oil is a weakly polar organic medium. The solubility of carboxylic acid molecules in it is limited and the dispersion is uneven. Traditional rigid SERS substrates are difficult to efficiently enrich trace amounts of polar carboxylic acid molecules from the oil phase.
[0007] (3) Insufficient long-term storage stability of the substrate: Although silver nanoparticles have the highest SERS enhancement factor, they are easily oxidized in the air, leading to signal attenuation; although pure gold nanoparticles have good stability, their enhancement factor is relatively low.
[0008] (4) In existing SERS substrate preparation methods, it is difficult to precisely control the particle size and distribution uniformity of nanoparticles: the conventional method for synthesizing gold and silver core-shell nanoparticles involves first preparing gold nanoparticle seeds, then growing a silver shell layer, and finally loading the synthesized nanoparticles onto the substrate. This method suffers from problems such as easy agglomeration of nanoparticles, uneven particle size distribution, and uncontrollable loading, which directly affect the signal reproducibility and detection accuracy of the SERS substrate.
[0009] Therefore, there is an urgent need to develop a novel SERS substrate that combines carboxyl-specific recognition, efficient enrichment through biphasic wetting, high SERS-enhanced activity, and long-term storage stability. Summary of the Invention
[0010] To address the problems in the prior art, this invention provides a surface-enhanced Raman spectroscopy substrate based on mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles, its preparation method, and its application. This substrate enables rapid and accurate on-site detection of the acid value of phosphate ester fire-resistant oils and effectively eliminates the interference of water content on the detection results.
[0011] This invention is achieved through the following technical solution: In a first aspect, the present invention provides a method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles, comprising: Step 1: Prepare thiolated polyethylene glycol and PDMS prepolymers; Step 2: Mix thiolized polyethylene glycol and PDMS prepolymer, add crosslinking agent and catalyst and stir. After curing, obtain PEG-SH / PDMS amphiphilic interpenetrating network gel with three-dimensional porous structure. Step 3: Prepare seed sol using gold nanoparticles as seeds. Immerse the PEG-SH / PDMS amphiphilic interpenetrating network gel in the seed sol to obtain a wet gel anchored with Au nanoparticles. Step 4: Immerse the wet gel anchored with Au nanoparticles in AgNO3 solution for a period of time at room temperature, and then add a reducing agent to the solution to carry out a reduction reaction to obtain a wet gel loaded with Au & Ag. Step 5: Immerse the Au & Ag loaded wet gel in 4-aminothiophenol ethanol / water solution and place it at room temperature to perform light-protected self-assembly. Then wash and dry to obtain the modified wet gel. Step 6: Under vacuum conditions, freeze-dry the modified wet gel to obtain a porous aerogel-like SERS substrate.
[0012] Preferably, in step 1, the specific process for preparing thiolated polyethylene glycol is as follows: polyethylene glycol is dissolved in anhydrous dichloromethane, mercaptoacetic acid, catalyst and 4-dimethylaminopyridine are added, and the reaction is carried out at room temperature under nitrogen protection. After the reaction is completed, the mixture is filtered, the precipitate is collected and vacuum dried to obtain thiolated polyethylene glycol with a thiolation rate ≥90%. The molecular weight of polyethylene glycol is 2000~5000 Da; the amount of mercaptoacetic acid is equal to the amount of polyethylene glycol; the catalyst is dicyclohexylcarbodiimide, and the amount used is 1.0~1.5 times the amount of PEG; the amount of 4-dimethylaminopyridine is 0.05~0.2 times the amount of PEG.
[0013] Preferably, in step 1, the preparation process of the PDMS prepolymer is as follows: vinyl-terminated polydimethylsiloxane and hydrogen-containing silicone oil are mixed at a mass ratio of 8:1 to 12:1, then a platinum catalyst is added, and the mixture is stirred evenly to obtain the PDMS prepolymer. The vinyl-terminated polydimethylsiloxane has a viscosity of 500~5000 cSt; the hydrogen content of the hydrogen-containing silicone oil is 0.3 wt%~0.8 wt%; the platinum catalyst is a chloroplatinic acid-isopropanol solution with a Pt content of 5~50 ppm of the total mass of PDMS.
[0014] Preferably, in step 2, the mass ratio of thiolated polyethylene glycol to PDMS prepolymer is (1:2) to (1:8). The crosslinking agent used is tetraethoxysilane, and the amount used is 2 wt% to 10 wt% of the mass of PEG-SH. The catalyst used was dibutyltin dilaurate, and the dosage was 0.5 wt% to 2 wt% of the TEOS mass. During curing, the temperature is 50~80℃ and the time is 8~24h; The PEG-SH / PDMS amphiphilic interpenetrating network gel has a pore size of 50~500nm and a porosity greater than 75%.
[0015] Preferably, in step 3, the preparation process of the seed sol is as follows: dissolve 0.01~0.05g of chloroauric acid in 100mL of deionized water, heat to boiling, then add 1~5mL of 1% sodium citrate solution, continue boiling for 10~20min until the solution changes from pale yellow to wine red, to obtain Au nanoparticle seed sol with a particle size of 13~20nm and an Au nanoparticle concentration of 0.1~0.5mg / mL; Soaking temperature is 30~50℃, time is 6~24h.
[0016] Preferably, in step 4, the soaking time is 2-6 hours; the reducing agent is 0.1 mol / L ascorbic acid solution, and the amount used is 1 / 5 to 1 / 2 of the volume of AgNO3 solution; during the reduction reaction, the temperature is 40-70℃ and the time is 30-120 minutes; the thickness of the silver shell layer is 3-12 nm.
[0017] Preferably, in step 5, the concentration of 4-aminothiophenol ethanol / water solution is 0.5~5 mmol / L, wherein the volume ratio of ethanol to water is 1:1; The self-assembly time is 6-24 hours; anhydrous ethanol is used for washing; nitrogen is used for drying.
[0018] Preferably, in step 6, during freeze drying, the vacuum degree is less than 20 Pa, the temperature is -20 to -50 °C, and the time is 24 to 72 h; the thickness of the obtained porous aerogel SERS substrate is 0.5 to 3 mm.
[0019] Secondly, the present invention also provides a porous aerogel-like SERS substrate obtained by the method described above for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles, wherein the particle size distribution range of Au & Ag nanoparticles in the porous aerogel-like SERS substrate is RSD < 8%; After the substrate was stored in room temperature air for 90 days, the ERS signal attenuation did not exceed 12% of the initial value. The substrate has a minimum detectable concentration of 0.01 mg KOH / g for carboxylic acids and a linear range of 0.01–0.5 mg KOH / g.
[0020] Thirdly, the present invention also provides an application of the porous aerogel-like SERS substrate in acid value detection.
[0021] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing a surface-enhanced Raman spectroscopy (SERS) substrate for loading gold and silver core-shell nanoparticles onto a mercapto-modified polyethylene glycol (PEG) / polydimethylsiloxane (PDMS) amphiphilic interpenetrating polymer network (APCN). First, an APCN gel is constructed using a sol-gel method and a crosslinking reaction. This is because APCNs are composed of interpenetrating hydrophilic and hydrophobic polymers, allowing for the simultaneous absorption of both polar and non-polar solutes. Furthermore, the amphiphilic APCN composed of PEG and PDMS has been shown to form stable microphase-separated structures, and its three-dimensional porous network can serve as a microreactor for nanoparticle synthesis, utilizing the spatial confinement effect of the pores to regulate the nucleation and growth processes of nanoparticles.
[0022] Secondly, pre-synthesized Au nanoparticle seeds were introduced into the gel network via impregnation diffusion. The strong affinity between the thiol groups and the Au nanoparticle surface was utilized to uniformly anchor them onto the network framework. The thiol groups also acted as anchoring points, fixing the Au nanoparticle seeds in specific positions. Subsequently, AgNO3 precursor solution and reducing agent solution were sequentially introduced into the gel network. During this immersion process, Ag... + Au nanoparticles are reduced and epitaxially grown on the surface of the seeds to form a silver shell. The three-dimensional pore structure of the gel network exerts a spatial confinement effect on the growth of the Ag shell. When the Ag shell grows to near the pore size, the growth rate is inhibited, thus limiting the thickness of the Ag shell to within the range allowed by the pores, thereby enabling precise control of the Ag shell thickness. Simultaneously, the uniformly distributed thiol anchoring points in the network ensure the uniform distribution of the Au nanoparticle seeds in three-dimensional space, ultimately yielding Au & Ag core-shell nanoparticles with consistent particle size and uniform distribution. This constitutes a highly enhanced and highly stable synergistic enhancement mechanism for the Au & Ag core-shell structure.
[0023] Third, since 4-ATP possesses both thiol (-SH, anchoring gold & silver surfaces) and amino (-NH2, capturing carboxyl groups) dual functional groups, this invention utilizes the thiol end of 4-ATP to self-assemble on Au & Ag surfaces, with the amino end exposed. Under heating conditions, it undergoes an amidation reaction with carboxylic acid molecules (R-COOH), achieving highly specific covalent capture and SERS detection of carboxylic acid substances. Attached Figure Description
[0024] Figure 1 This is a flowchart of a method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles according to the present invention. Figure 2This is a synthesis diagram of a surface-enhanced Raman spectroscopy substrate prepared by a method for preparing gold and silver core-shell nanoparticles based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel according to the present invention. Detailed Implementation
[0025] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification.
[0026] Exemplary embodiments of the present invention will now be described with reference to the accompanying drawings. However, the present invention may be embodied in many different forms and is not limited to the embodiments described herein. These embodiments are provided to fully and completely disclose the invention and to fully convey its scope to those skilled in the art. The terminology used in the exemplary embodiments illustrated in the drawings is not intended to limit the invention. In the drawings, the same units / elements are referred to by the same reference numerals.
[0027] Unless otherwise stated, the terms used herein (including technical terms) have their common meaning as understood by one of ordinary skill in the art. Furthermore, it is understood that terms defined in commonly used dictionaries should be understood to have a meaning consistent with the context of their relevant field, and not to be interpreted as having an idealized or overly formal meaning.
[0028] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.
[0029] This invention discloses a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles, referring to... Figure 1 , 2 ,include: Step 1: Prepare thiol-modified polyethylene glycol and PDMS prepolymers, specifically: Step 101, the specific process for preparing thiolated polyethylene glycol (PEG-SH) is as follows: Polyethylene glycol is dissolved in anhydrous dichloromethane, and thioglycolic acid, a catalyst, and 4-dimethylaminopyridine are added. The reaction is carried out at room temperature under nitrogen protection. After the reaction, the mixture is filtered, and the precipitate is collected and vacuum dried to obtain thiolated polyethylene glycol (PEG-SH) with a thiolation rate ≥90%. Specifically, the molecular weight of polyethylene glycol (PEG) is 2000~5000 Da, preferably 2000 Da; the amount of thioglycolic acid is equal to the amount of polyethylene glycol; the catalyst is dicyclohexylcarbodiimide (DCC), used in an amount 1.0~1.5 times the amount of PEG; and the amount of 4-dimethylaminopyridine (DMAP) is 0.05~0.2 times the amount of PEG. The thiol content of PEG-SH is determined by the Ellman method, and the thiolation rate should be ≥90%.
[0030] Step 102, the preparation process of the PDMS prepolymer is as follows: vinyl-terminated polydimethylsiloxane and hydrogen-containing silicone oil are mixed at a mass ratio of 8:1 to 12:1 (preferably 10:1), then a platinum catalyst is added, and the mixture is stirred evenly to obtain the PDMS prepolymer. The viscosity of the vinyl-terminated polydimethylsiloxane is 500 to 5000 cSt, preferably 1000 cSt; the hydrogen content of the hydrogen-containing silicone oil is 0.3 wt% to 0.8 wt%; the platinum catalyst is a chloroplatinic acid-isopropanol solution, and the Pt content is 5 to 50 ppm of the total mass of PDMS, preferably 10 ppm.
[0031] Step 2: Mix thiol-modified polyethylene glycol and PDMS prepolymer, add crosslinking agent and catalyst, stir, and cure to obtain a PEG-SH / PDMS amphiphilic interpenetrating network gel with a three-dimensional porous structure. The mass ratio of thiol-modified polyethylene glycol to PDMS prepolymer is (1:2) to (1:8), preferably 1:4; the crosslinking agent is tetraethoxysilane (TEOS), used in an amount of 2 wt% to 10 wt% of the PEG-SH mass, preferably 5 wt%; the catalyst is dibutyltin dilaurate (DBTDL), used in an amount of 0.5 wt% to 2 wt% of the TEOS mass, preferably 1 wt%; the curing temperature is 50 to 80℃, and the time is 8 to 24 h, preferably 60℃ for 12 h; the pore size of the PEG-SH / PDMS amphiphilic interpenetrating network gel is 50 to 500 nm, and the porosity is greater than 75%.
[0032] Step 3: Prepare a seed sol using gold nanoparticles as seeds. Immerse the PEG-SH / PDMS amphiphilic interpenetrating network gel in the seed sol to obtain a wet gel anchored with Au nanoparticles. Specifically: Step 301, the preparation process of seed sol is as follows: Dissolve chloroauric acid (HAuCl4·3H2O, 0.01~0.05g, preferably 0.025g) in 100mL of deionized water, heat to boiling, quickly add 1% (w / v) sodium citrate solution (1~5mL, preferably 2mL), continue boiling for 10~20 minutes until the solution changes from pale yellow to wine red, and Au nanoparticle seed sol with a particle size of 13~20nm is obtained.
[0033] Step 302: Cut the PEG-SH / PDMS amphiphilic interpenetrating network gel into small pieces of 1cm × 1cm × 0.2~0.5cm, immerse them in the obtained Au nanoparticle seed sol (Au nanoparticle concentration approximately 0.1~0.5mg / mL), and soak them at 30~50℃ (preferably 40℃) for 6~24 hours (preferably 12 hours) to obtain a wet gel anchored with Au nanoparticles. During this process, the strong affinity between the thiol groups (-SH) on the PEG-SH chain and the surface of the Au nanoparticles (Au-S bonds) is utilized to uniformly anchor the Au nanoparticle seeds to the surface of the gel network framework through chemical bonds. After removal, wash three times with deionized water to remove any physically adsorbed but unanchored Au nanoparticle seeds.
[0034] Step 4: At room temperature, immerse the wet gel anchored with Au nanoparticles in an AgNO3 solution for a period of time. Then, add a reducing agent dropwise to the solution to carry out a reduction reaction, obtaining a wet gel loaded with Au and Ag. Specifically: The wet gel anchored with Au nanoparticles was immersed in 10-20 mL of 0.01 mol / L AgNO3 solution at room temperature for 2-6 hours to allow the Ag nanoparticles to settle. + The ascorbic acid fully diffuses into the gel network and adsorbs onto the surface of the Au nanoparticle seeds. Subsequently, a 0.1 mol / L ascorbic acid solution (reducing agent, used in amounts of 1 / 5 to 1 / 2 the volume of the AgNO3 solution) is slowly added dropwise to the system, and reduction is carried out at 40–70°C (preferably 60°C) for 30–120 minutes (preferably 60 minutes). + The Au nanoparticles were reduced and epitaxially grown on the surface of the seeds to form a silver shell.
[0035] In this process, the three-dimensional porous structure of the interpenetrating network acts as a "microreactor," exerting a spatial confinement effect: when the Ag shell grows to near the network pore size, the steric hindrance and diffusion restriction of the pore walls inhibit further growth of the Ag shell, thus controlling the Ag shell thickness within the range of 3–12 nm (preferably 5–8 nm). Simultaneously, due to the uniform distribution of Au nanoparticle seeds in the three-dimensional network, the growth of the Ag shell occurs synchronously throughout the entire network, ensuring the uniformity of particle size and distribution of the Au & Ag core-shell nanoparticles. During the reaction, the solution color gradually changes from wine red to orange-yellow, and finally to brownish-yellow, indicating the successful formation of the Au & Ag core-shell structure. After the reaction, the wet gel is removed and washed three times with deionized water to remove unreacted Ag. + and residual reducing agents.
[0036] Step 5: Immerse the Au & Ag-loaded wet gel in 4-aminothiophenol ethanol / water solution and allow it to self-assemble in the dark at room temperature. After washing and drying, the modified wet gel is obtained. Specifically: The Au & Ag loaded wet gel was immersed in a 0.5–5 mmol / L (preferably 1 mmol / L) solution of 4-aminothiophenol (4-ATP) in ethanol / water (1:1 volume ratio) and self-assembled at room temperature in the dark for 6–24 hours (preferably 12 hours). The thiol terminus (-SH) of 4-ATP was anchored to the surface of the Au & Ag nanoparticles (forming Au-S or Ag-S bonds), while the amino terminus (-NH2) was exposed for subsequent capture of carboxylic acid molecules (R-COOH). After removal, the gel was washed twice with anhydrous ethanol and dried under nitrogen.
[0037] Step 6: Under vacuum conditions, freeze-dry the modified wet gel to obtain a porous aerogel-like SERS substrate. The vacuum level is less than 20 Pa, the temperature is -20 to -50 °C, and the time is 24 to 72 hours. The thickness of the obtained porous aerogel-like SERS substrate is 0.5 to 3 mm.
[0038] This invention addresses the problems of nanoparticle agglomeration, uneven particle size distribution, and uncontrollable loading in traditional methods by employing a preparation strategy of first constructing a network and then confining it for synthesis. Unlike existing methods that synthesize nanoparticles first and then load them onto a substrate, this invention first constructs a PEG-SH / PDMS amphiphilic interpenetrating network gel, then uses its three-dimensional porous network as a "microreactor" to synthesize Au & Ag core-shell nanoparticles in situ within the pores. The spatial confinement effect of the interpenetrating network channels allows for precise control of the Ag shell thickness within the 3–12 nm range, ensuring uniform distribution of nanoparticles throughout the network and thus improving the reproducibility and batch consistency of the substrate.
[0039] This invention is the first to combine a PEG-SH / PDMS amphiphilic interpenetrating network with Au & Ag core-shell nanoparticles for use as a SERS substrate. No prior art has reported the use of a PEG-SH / PDMS amphiphilic interpenetrating network as a three-dimensional carrier matrix for SERS-active nanoparticles. This invention utilizes the hydrophilicity of PEG-SH and the hydrophobicity of PDMS to construct an amphiphilic interpenetrating network, thereby achieving the function of efficiently extracting polar carboxylic acid molecules from fire-resistant oils and integrating it with SERS enhancement. Simultaneously, a synergistic fixation strategy of thiol chemical anchoring and spatially confined synthesis avoids the defects of nanoparticle agglomeration and detachment. This is because this invention uses pre-placed thiol groups (-SH) on the PEG-SH chain as chemical anchoring points for Au nanoparticle seeds, ensuring uniform distribution of the seeds in the three-dimensional network; subsequently, an Ag shell is grown in situ within the confined space, achieving the integration of in-situ chemical bond anchoring and size-controlled growth of the nanoparticles. Furthermore, the Ag shell provides the highest SERS enhancement factor (~10). 7 ~10 8 The Au core and the Au core provide chemical stability and antioxidant properties. This invention uses the two in synergy to ensure high detection sensitivity and solve the problem of signal attenuation caused by the easy oxidation of pure Ag nanoparticles in air.
[0040] Secondly, this invention also discloses a porous aerogel-like SERS substrate obtained by the method described above for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles. The porous aerogel-like SERS substrate was tested and its performance was evaluated, with the following results: (1) Scanning electron microscopy (SEM) showed that the PEG-SH / PDMS amphiphilic interpenetrating network has a highly developed three-dimensional porous structure with pore size distribution between 50 and 500 nm and porosity greater than 75%.
[0041] (2) Observation by transmission electron microscopy (TEM) showed that the Au & Ag core-shell nanoparticles were spherical, with Au core particle size of 13~20nm and Ag shell thickness of 3~12nm (preferably 5~8nm), uniform particle size distribution, and relative standard deviation (RSD) <8%.
[0042] (3) Energy dispersive X-ray spectroscopy (EDS) elemental mapping confirmed that Au and Ag elements were uniformly distributed within the gel network. Compared with the traditional "synthesis first, loading later" method, the Au & Ag nanoparticles prepared by the network-first, synthesis-later method of this invention have a narrower particle size distribution range (RSD reduced by about 40%) and significantly reduced agglomeration.
[0043] (4) Fourier transform infrared spectroscopy (FTIR) shows that PEG-SH has a characteristic absorption peak of -SH at ~2550 cm⁻¹. - ¹) The absorption peak disappears or weakens after anchoring Au and Ag, confirming the formation of Au-S / Ag-S bonds; the characteristic absorption peak of -NH2 (~1620 cm⁻¹) appears after 4-ATP modification. - ¹ and ~3400cm - ¹), indicating that 4-ATP grafting was successful.
[0044] (5) After the substrate is stored in air at room temperature for 90 days, the ERS signal decay does not exceed 12% of the initial value, and the signal retention rate is greater than 88%.
[0045] (6) Using benzoic acid as a probe molecule, the substrate of this invention can detect carboxylic acid substances with a minimum concentration of 0.01 mg KOH / g (based on acid value), and the linear range is 0.01~0.5 mg KOH / g, which completely covers the acid value range of fire-resistant oil in operation (≤0.15 mg KOH / g), which is superior to the current standard method in the power industry.
[0046] (7) Using Rhodamine 6G (R6G) as the probe molecule, the SERS enhancement factor (EF) of this invention can reach 1×10⁻⁶. 7 ~1×10 8 .
[0047] (8) In a mixed fire-resistant oil sample containing carboxylic acids (benzoic acid, 10 mg / L), phenols (2,6-di-tert-butyl-p-cresol, 100 mg / L), and esters (tricresyl phosphate, 1000 mg / L), a significant SERS signal was generated only at the characteristic peak of carboxylic acids, while other interfering substances showed no obvious response. The amidation reaction of the amino and carboxyl groups of 4-ATP endows the substrate with a high specificity for recognizing carboxylic acids.
[0048] (9) The relative standard deviation (RSD) of SERS signals at different points on the same substrate (n=10) is <5%; the RSD of different batches of substrates (n=5) is <8%. Compared with the traditional "synthesis first, loading later" method (RSD>8% for the same substrate, RSD>12% between batches), the reproducibility of the present invention is significantly improved.
[0049] Thirdly, this invention also discloses an application of the porous aerogel SERS substrate in acid value detection. Specifically, the porous aerogel SERS substrate is placed in the sample cell of a portable Raman spectrometer, and 1 mL of the fire-resistant oil sample to be tested is added. The sample is incubated at 60°C for 5 minutes, then excited with a 785 nm laser (power 10 mW, integration time 2 seconds, cumulative 3 times), and the SERS spectrum is acquired. The true acid value is calculated using the above detection method. The entire detection process can be completed within 10 minutes, with a sample consumption of <2 mL.
[0050] Example 1 1. Preparation of porous aerogel-like SERS substrate Step 1, Step 101, Synthesis of PEG-SH PEG2000 (10.0 g, 5.0 mmol) was weighed and dissolved in 100 mL of anhydrous dichloromethane. Thioglycolic acid (0.46 g, 5.0 mmol), DCC (1.55 g, 7.5 mmol, 1.5 equiv), and DMAP (0.061 g, 0.5 mmol, 0.1 equiv) were added. The mixture was stirred at room temperature for 24 hours under nitrogen protection. After the reaction was complete, the insoluble matter (dicyclohexylurea) was removed by filtration. The filtrate was slowly added dropwise to 500 mL of cold diethyl ether with stirring to precipitate the precipitate. The precipitate was collected, washed twice with diethyl ether, and dried under vacuum at 40 °C for 12 hours to obtain 8.5 g of white powder PEG-SH (yield approximately 82%). The thiol content was determined to be 0.48 mmol / g by the Ellman method, and the thiolization rate was approximately 96%.
[0051] Step 102, Preparation of PDMS prepolymer: Mix 8.0g of vinyl-terminated PDMS (viscosity 1000cSt) with 0.8g of hydrogen-containing silicone oil (hydrogen content 0.5wt%) (mass ratio 10:1), add chloroplatinic acid-isopropanol solution (Pt content is 10ppm of total PDMS mass), stir evenly to obtain PDMS prepolymer.
[0052] Step 2, Construction of the interpenetrating network: Dissolve 2.0 g of PEG-SH in 5 mL of anhydrous ethanol, and mix with 8.8 g of the above PDMS prepolymer (PEG-SH:PDMS mass ratio ≈ 1:4.4). Add 0.10 g of TEOS (5 wt% of PEG-SH) and 1 mg of DBTDL (1 wt% of TEOS). After stirring evenly, pour into a 1 mm thick PTFE mold and cure at 60 °C for 12 hours. Remove the gel and wash three times with anhydrous ethanol to remove unreacted substances, obtaining a PEG-SH / PDMS amphiphilic interpenetrating network gel. SEM showed a pore size distribution of 100–300 nm and a porosity of approximately 82%.
[0053] Step 3 Step 301, Preparation of Au nanoparticle seeds: Dissolve 0.025 g of HAuCl4·3H2O in 100 mL of deionized water, heat to boiling, quickly add 2 mL of 1% (w / v) sodium citrate solution, and continue boiling for 15 minutes. The solution changes from pale yellow to wine red, yielding Au nanoparticle seed sol. UV-Vis spectroscopy shows a characteristic absorption peak at 520 nm, and TEM shows a particle size of approximately 15 ± 2 nm.
[0054] Step 302, Anchoring of Au nanoparticle seeds within the network: The PEG-SH / PDMS amphiphilic interpenetrating network gel obtained in step 1.2 is cut into small pieces of 1cm × 1cm × 0.3cm and immersed in 10mL of the above Au nanoparticle seed sol at 40℃ for 12 hours. After removal, it is washed three times with deionized water for 5 minutes each time to remove Au nanoparticle seeds that were physically adsorbed but not anchored.
[0055] Step 4: Immerse the gel anchored with Au nanoparticle seeds in 15 mL of 0.01 mol / L AgNO3 solution and soak at room temperature for 4 hours to allow the Ag nanoparticles to settle. + Sufficient diffusion was achieved. Subsequently, 3 mL of 0.1 mol / L ascorbic acid solution (1 / 5 the volume of AgNO3 solution) was slowly added dropwise at a rate of 0.5 mL / min, and the reaction was carried out at 60 °C for 60 minutes. The solution color gradually changed from wine red to orange-yellow. TEM showed an Au & Ag core-shell structure, with Au cores approximately 15 nm in diameter, Ag shells approximately 6 nm thick (ranging from 5 to 8 nm), a total particle size of approximately 27 nm, and a particle size RSD of approximately 6.5%. After the reaction was complete, the gel was removed and washed three times with deionized water.
[0056] Step 5: Immerse the Au & Ag loaded gel in 10 mL of 1 mmol / L 4-ATP ethanol / water (volume ratio 1:1) solution and allow it to self-assemble at room temperature in the dark for 12 hours. After removal, wash twice with anhydrous ethanol and dry under nitrogen.
[0057] Step 6: Place the substrate obtained in Step 1.5 in a freeze dryer, dry at -40°C for 48 hours under a vacuum of <10 Pa to obtain a porous aerogel-like SERS substrate. The obtained substrate is approximately 1 mm thick and is a dark brown porous sponge-like solid.
[0058] 2. Performance testing of the obtained porous aerogel-like SERS substrate. 2.1 Sensitivity Test Benzoic acid-fire-resistant oil standard solutions were prepared with concentrations equivalent to acid values of 0.005, 0.01, 0.02, 0.05, 0.1, 0.2, and 0.5 mg KOH / g, respectively. 1 mL of each concentration of standard oil sample was added to the 4-ATP modified substrate prepared in Example 1, and the solutions were incubated at 60°C for 5 minutes. Detection was performed using a portable Raman spectrometer (785 nm laser, 10 mW power, integration time 2 seconds, cumulative 3 times).
[0059] The results showed that the characteristic peak of benzoic acid (~1410 cm⁻¹) was present. - ¹, COO -The intensity of the characteristic peak (symmetric stretching vibration) increases with increasing concentration. Within the range of 0.01–0.5 mg KOH / g, the intensity of the characteristic peak shows a good linear relationship with the acid value (R² = 0.992). The lowest detectable concentration is 0.01 mg KOH / g (signal-to-noise ratio S / N = 3).
[0060] 2.2 Selective Testing Prepare a mixed fire-resistant oil sample containing benzoic acid (10 mg / L, equivalent to an acid value of ~0.07 mg KOH / g), 2,6-di-tert-butyl-p-cresol (100 mg / L), and tricresyl phosphate (1000 mg / L). Detect the fire-resistant oil according to method 2.1.
[0061] Result: Only at ~1410cm - A distinct characteristic peak for carboxylic acids was observed at ¹, while phenols and esters showed characteristic peaks in their respective regions (phenols ~3650 cm⁻¹). - ¹, Esters ~1730cm - ¹) No significant SERS response was observed, demonstrating that the 4-ATP modified substrate has excellent specific recognition ability for carboxylic acids.
[0062] 2.3 Reproducibility Test Ten different sites were randomly selected on the same 4-ATP modified substrate for SERS analysis of benzoic acid-fired oil samples at the same concentration (0.1 mg KOH / g). The 10 sites were located at approximately 1410 cm⁻¹. - The relative standard deviation (RSD) of the characteristic peak intensity at ¹ was 4.6%. The RSD of the five substrates (n=5) prepared from different batches was 7.8%. In comparison, the control substrate (Comparative Example 2) prepared using the traditional “synthesis-then-loading” method had an RSD of 9.2% for the same substrate and an RSD of 13.5% between batches.
[0063] 2.4 Storage Stability Test The substrate prepared in Example 1 was stored at room temperature and atmospheric environment (temperature 25±2℃, relative humidity 40%~60%), and was taken out at 0, 15, 30, 45, 60, 75 and 90 days respectively, and SERS was detected by 0.1mgKOH / g benzoic acid-fire-resistant oil standard solution (n=3 parallel samples).
[0064] The results showed that after 90 days of storage, ~1410cm - The characteristic peak intensity at point ¹ is 89.1% of the initial value (attenuation of 10.9%), demonstrating that the substrate of this invention has excellent long-term storage stability.
[0065] In summary, the preparation method of this invention uses an interpenetrating network (IPN) confinement synthesis strategy to ensure the uniformity of Au & Ag nanoparticle size and distribution. Simultaneously, the synergistic effect of the Au & Ag core-shell structure and the IPN's physical confinement effect ensures that the SERS signal decays by less than 12% after 90 days of storage in air. This preparation method utilizes the confinement effect of the IPN's channels to in-situ control the nanoparticle size, eliminating the need for complex external field control methods. The conditions are mild, suitable for batch preparation, and the resulting substrate exhibits high detection sensitivity, particularly for the efficient extraction of polar carboxylic acid molecules from fire-resistant oils. This is because the PEG-SH / PDMS amphiphilic IPN can actively extract polar carboxylic acid molecules from fire-resistant oils, shortening the adsorption equilibrium time to 3-5 minutes and resulting in a rapid enrichment response. Furthermore, the amidation reaction of the 4-ATP amino and carboxyl groups endows the substrate with high specificity for carboxylic acid substances, making it unaffected by interfering substances such as phenols and esters in complex fire-resistant oil matrices (phosphate ester fire-resistant oils, mineral insulating oils, or other oils), demonstrating excellent selectivity. Furthermore, the substrate size can be cut to size, and it can be used in conjunction with a handheld / portable Raman spectrometer, making it suitable for rapid on-site screening in substations and power plants.
[0066] The above description is merely a preferred embodiment of the present invention and is not intended to limit the technical solution of the present invention in any way. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can be modified and replaced in several simple ways, and these modifications and replacements are all within the scope of protection covered by the claims.
Claims
1. A method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles, characterized in that, include: Step 1: Prepare thiolated polyethylene glycol and PDMS prepolymers; Step 2: Mix thiolized polyethylene glycol and PDMS prepolymer, add crosslinking agent and catalyst and stir. After curing, obtain PEG-SH / PDMS amphiphilic interpenetrating network gel with a three-dimensional porous structure. Step 3: Prepare seed sol using gold nanoparticles as seeds. Immerse the PEG-SH / PDMS amphiphilic interpenetrating network gel in the seed sol to obtain a wet gel anchored with Au nanoparticles. Step 4: Immerse the wet gel anchored with Au nanoparticles in AgNO3 solution for a period of time at room temperature, and then add a reducing agent to the solution to carry out a reduction reaction to obtain a wet gel loaded with Au & Ag. Step 5: Immerse the Au & Ag loaded wet gel in 4-aminothiophenol ethanol / water solution and place it at room temperature to perform light-protected self-assembly. Then wash and dry to obtain the modified wet gel. Step 6: Under vacuum conditions, freeze-dry the modified wet gel to obtain a porous aerogel-like SERS substrate.
2. The method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles according to claim 1, characterized in that, In step 1, the specific process for preparing thiolated polyethylene glycol is as follows: polyethylene glycol is dissolved in anhydrous dichloromethane, mercaptoacetic acid, catalyst and 4-dimethylaminopyridine are added, and the reaction is carried out at room temperature under nitrogen protection. After the reaction is completed, the mixture is filtered, the precipitate is collected and vacuum dried to obtain thiolated polyethylene glycol with a thiolation rate ≥90%. The molecular weight of polyethylene glycol is 2000~5000 Da; the amount of mercaptoacetic acid is equal to the amount of polyethylene glycol; the catalyst is dicyclohexylcarbodiimide, and the amount used is 1.0~1.5 times the amount of PEG; the amount of 4-dimethylaminopyridine is 0.05~0.2 times the amount of PEG.
3. The method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles according to claim 2, characterized in that, In step 1, the preparation process of PDMS prepolymer is as follows: vinyl-terminated polydimethylsiloxane and hydrogen-containing silicone oil are mixed at a mass ratio of 8:1 to 12:1, then a platinum catalyst is added, and the mixture is stirred evenly to obtain PDMS prepolymer. The viscosity of the vinyl-terminated polydimethylsiloxane is 500~5000 cSt; the hydrogen content of the hydrogen-containing silicone oil is 0.3wt%~0.8wt%; the platinum catalyst is a chloroplatinic acid-isopropanol solution with a Pt content of 5~50 ppm of the total mass of PDMS.
4. The method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles according to claim 1, characterized in that, In step 2, the mass ratio of thiolated polyethylene glycol to PDMS prepolymer is (1:2) to (1:8). The crosslinking agent used is tetraethoxysilane, and the amount used is 2 wt% to 10 wt% of the mass of PEG-SH. The catalyst used was dibutyltin dilaurate, and the dosage was 0.5 wt% to 2 wt% of the TEOS mass. During curing, the temperature is 50~80℃ and the time is 8~24h; The PEG-SH / PDMS amphiphilic interpenetrating network gel has a pore size of 50~500nm and a porosity greater than 75%.
5. The method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles according to claim 4, characterized in that, In step 3, the seed sol is prepared as follows: 0.01~0.05g of chloroauric acid is dissolved in 100mL of deionized water, heated to boiling, and then 1~5mL of 1% sodium citrate solution is added. The mixture is boiled for 10~20min until the solution changes from pale yellow to wine red, thus obtaining Au nanoparticle seed sol with a particle size of 13~20nm and an Au nanoparticle concentration of 0.1~0.5mg / mL. Soaking temperature is 30~50℃, time is 6~24h.
6. The method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles according to claim 1, characterized in that, In step 4, the soaking time is 2-6 hours; the reducing agent is 0.1 mol / L ascorbic acid solution, and the amount used is 1 / 5 to 1 / 2 of the volume of AgNO3 solution; during the reduction reaction, the temperature is 40-70℃ and the time is 30-120 minutes; the thickness of the silver shell layer is 3-12 nm.
7. The method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles according to claim 1, characterized in that, In step 5, the concentration of 4-aminobenzylthiophenol ethanol / water solution is 0.5~5 mmol / L, wherein the volume ratio of ethanol to water is 1:1; The self-assembly time is 6-24 hours; anhydrous ethanol is used for washing; nitrogen is used for drying.
8. The method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles according to claim 1, characterized in that, Step 6: During freeze drying, the vacuum degree is less than 20 Pa, the temperature is -20 to -50 °C, and the time is 24 to 72 h; the thickness of the obtained porous aerogel SERS substrate is 0.5 to 3 mm.
9. A porous aerogel-like SERS substrate obtained by the method for preparing a surface-enhanced Raman spectroscopy substrate based on a mercapto-modified polyethylene glycol / polydimethylsiloxane amphiphilic interpenetrating network gel loaded with gold & silver core-shell nanoparticles as described in any one of claims 1 to 8, characterized in that, The particle size distribution range of Au & Ag nanoparticles in the porous aerogel-like SERS substrate is RSD < 8%; After being stored in room temperature air for 90 days, the ERS signal of the substrate decreased by no more than 12% of its initial value. The substrate has a minimum detectable concentration of 0.01 mg KOH / g for carboxylic acids and a linear range of 0.01–0.5 mg KOH / g.
10. The application of the porous aerogel-like SERS substrate as described in claim 9 in acid value detection.
Citation Information
Patent Citations
Raman spectrum-based device and method for detecting inferior oil doped in edible oil
CN119827479A